Cooperation between head teachers and professional school counsellors in Slovenian schools - Gregorčič Mrvar, Petra (Array, 2019)
The characteristics of cooperation between head teachers and school counsellors are presented theoretically and empirically. Distributed leadership means that head teachers do not lead schools through school-based educators but rather together with them, with school counsellors playing an important role. Numerous research studies demonstrate that a strong head teacher–school counsellor relationship is a crucial component of meeting the vision, goals and well-being of the school. The findings of our research study, conducted among head teachers and school counsellors, show positive attitudes of both groups towards mutual cooperation. Both considered the cooperation to be good or very good, the head teachers rated it even better. It is interesting to observe that the head teachers found more support in school counsellors than vice versa. Also, more of the head teachers said they saw school counsellors as partners than did the school counsellors. It thus remains to be seen how school counsellors’ perception of the school leadership’s support in their work could be strengthened and how head teachers could be encouraged to support the work of the school counselling service even more, so that this relationship becomes reciprocal and that each party’s ability to perform their work will be enhanced by the strong relationship.